EFEKTIVITAS PERAN PENYULUH AGAMA ISLAM DALAM PENERAPAN HUKUM PERKAWINAN ISLAM DI MASYARAKAT PEDESAAN (Studi Kasus di Kecamatan Mare Kabupaten Bone) - Syamsuddin, Syamsuddin; Fathurahman, H. (Jurnal Ar-Risalah, 2021)
This research led to the application of the law of Islamic marriage in rural communities. The purpose of this research is to know the application of Islamic marriage legal on rural communities in the Mare, the effectiveness of the role of extension officers in the implementation of Islamic law in the Islamic marriage Mare and barriers in the application of the law Islamic marriage in rural communities in district Mare Bone Regency. The role of religion in the legal application of extension officers marriage Islam in Mare Bone Regency have not fully maximized. The countryside has not been entirely untouched by the public. The form of the application made by extension officers have not completely evenly in the Mare and the methods used in extension is not effective. In addition, the guidance material is delivered poorly understood by the public, so that the impact on the lack of implementation of relevant Islamic marriage law with the provisions of legislation in force in Indonesia. Constraints in the implementation of the Islamic law of marriage in society is a condition of the Mare was lacking presence and outreach programs respond to the low level of education of rural people in district Mare Bone Regency.